The comparative gene expression concern to the seed pigmentation in maize ( L.) - Kyu Jin Sa; Ik-Young Choi; Ju Kyong Lee (Genomics & Informatics)
Maize seed pigmentation is one of the important issue to develop maize seed breeding. The differently gene expression was characterized and compared for three inbred lines, such as the pigment accumulated seed (CM22) and non-pigmented seed (CM5 and CM19) at 10 days after pollination. We obtained a total of 63,870, 82,496, and 54,555 contigs by de novo assembly to identify gene expression in the CM22, CM5, and CM19, respectably. In differentially expressed gene analysis, it was revealed that 7,044 genes were differentially expressed by at least two-fold, with 4,067 upregulated in colored maize inbred lines and 2,977 upregulated in colorless maize inbred lines. Of them,18 genes were included to the anthocyanin biosynthesis pathways, while 15 genes were upregulated in both CM22/5 and CM22/19. Additionally, 37 genes were detected in the metabolic pathway concern to the seed pigmentation by BINs analysis using MAPMAN software. Finally, these differently expressed genes may aid in the research on seed pigmentation in maize breeding programs.